Effects of Surgical Stress on Serum Cortisol Level: A Comparative Study between Elective and Emergency Surgery - Selimuzzaman, SM; Begum, Noorzahan; Islam, Nadira; Begum, Shelina (Journal of Bangladesh Society of Physiologist, 2008)
The study was designed to observe the effects of surgical stress on serum level of cortisol in patients undergoing surgical treatment and to find out any differences in hormonal response between elective and emergency surgical procedures. A total number of 60 male subjects aged between 18 and 45 years were included in the study. Of them, 20 were healthy control (Group I), 20 underwent elective surgical treatment (Group II) and emergency surgical interventions were applied in rest 20 subjects (Group III). Study Groups were further divided into subgroups A (preoperative samples were collected 1- hour before operation), B (postoperative samples were collected 1-hour after the end of the operation) and C (postoperative samples were collected 24-hours after operation).Serum cortisol level was estimated by invitro-immunolytic test.Statistical analysis was done by paired, unpaired ‘t' test and regression analysis. The preoperative mean serum cortisol concentration in elective surgical cases was almost similar to that of healthy control. On the contrary, in the emergency surgical cases, a significantly increased mean cortisol level were observed (I vs IIIA and IIA vs IIIA; P < 0.05). The serum cortisol concentrations were increased both in elective and emergency surgical cases after operations but the magnitude of rise was more marked in emergency group of patients (IIB vs IIIB; P < 0.05). Therefore, this study reveals that surgical intervention causes increase in serum cortisol which is more marked in emergency procedure. Key Words: Stress; Cortisol; Surgery DOI:10.3329/jbsp.v2i0.981 J Bangladesh Soc Physiol. 2007 Dec;(2): 28-33.